ENSHRINEMENT SPATIAL PATTERN IN BUMIAYU TEMPLES (DESCRIPTION OF ENVIRONMENTAL ADAPTATION IN WET LAND) - Sondang Martini Siregar (Chelonian Research Foundation, 2024)
The Bumiayu temple is located in wetlands, but the temples are protected from puddles. The problem that arises are a) how is the location of Bumiayu temples, b) how is the network in Bumiayu temples area and c) how is the distribution of the Bumiayu temples. The purpose of this study was to analyze the spatial pattern of the Bumiayu enshrinement which shows that the people-built temples had adapted to nature. The specific aims are to analyze the morphography, morphometry, landform of the Bumiayu temples, b) to analyze water activity in Bumiayu temples c) to analyze the distribution and orientation of the Bumiayu temples. The qualitative method is used with descriptive and expansive reasoning, precisely the order using the Widyamanti classification (2016). The distribution/orientation of the temples uses data proximity analysis. The results showed that the Bumiayu temple area was lowland with an elevation of 11 masl - 20 masl and was on a rather sloping (8 % - 13 %). The landform consists of the river terrace, natural embankment, swamp. The enshrinement area consists of 4 rooms bordered by rivers and lakes. Location is in a group position and surrounded by canals that tributaries of the Lematang River. In the past, the community had managed the environment. They made canals to regulate water and transportation facilities in Bumiayu temple area. In addition, the canal also serves to fulfil practical and ritual needed. Keywords: pattern, wet land, temple Bumiayu